Faculty Training Needs Analysis - Panen, Vencita; Panen, Ronnie; Buena Agua, Juvy; Jayme, Kathleen Wynette (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study conducted a Training Needs Analysis to determine the competency levels and priority professional development needs of faculty members at the NYK-TDG Maritime Academy. It was conceptually anchored in Training Needs Analysis and the Technological Pedagogical Content Knowledge framework. Using a descriptive quantitative research design, the study gathered data from faculty members representing different departments and areas of specialization through a structured survey form using a four-point Likert scale. Frequency, percentage, weighted mean, standard deviation, ranking, and gap analysis were used to analyze the data. The findings showed that faculty members were generally competent in most assessed areas. Faculty Leadership and Ethics obtained the highest mean score of 3.40, followed by Classroom Management at 3.25 and Teaching and Learning Strategies at 3.20. Outcomes-Based Education, Educational Technology Integration, Academic Advising and Mentoring, and Extension Services were identified as moderate training priorities. In contrast, Assessment and Evaluation obtained a mean of 2.35, Artificial Intelligence in Education obtained 2.10, and Research Writing and Publication received the lowest mean of 1.95, making it the most critical professional development need. The study concluded that faculty members possess strong foundational competencies in instruction, leadership, and classroom management but require targeted and sustained development in research, artificial intelligence integration, and assessment practices. It recommended annual training needs assessments, output-based training, continued mentoring, institutional alignment, and systematic monitoring of faculty development outcomes. The study supports Sustainable Development Goal 4 by strengthening the quality of maritime education and Sustainable Development Goal 9 by promoting responsible technological integration and academic innovation. Its sustainability impact lies in supporting long-term faculty development, instructional quality, research productivity, accreditation readiness, and evidence-based institutional planning.